Excavations at the Gilligan's Island shelters (5FN1592), Fort Carson Military Reservation (FCMR), Fremont County, Colorado - Anderson, Cody Mitchell, author; Eighmy, Jeffrey L., advisor; Zier, Christian J., committee member; Fiege, Mark T., committee member (Colorado State University. Libraries, 2008)
This thesis examines the surface and subsurface archaeological work undertaken in 2002 at the Gilligan's Island site (5FN1592), located at the base of the Rocky Mountains on the Fort Carson Military Reservation, eastern Fremont County, Colorado. Permission was granted by Fort Carson to conduct an excavation at this site in order to determine its potential to produce significant subsurface occupational remains. Excavations focused on two connecting rock shelters at the base of a prominent cliff face. Four interconnecting grid units were positioned in a trench-like fashion through the central midline of each shelter proper. Deposition of excavated units ranges up to 1.3 meters in depth. These trenches exposed deeply stratified prehistoric materials including multiple intact features. The radiocarbon data (based on conventional uncalibrated dates) identified three prehistoric cultural components: Middle Archaic period (ca. 4240-3010 B.P.), Late Archaic period (ca. 2230-1880 B.P.), and Developmental period (ca. 1390- 1070 B.P.). A historic component is also evident and is associated with probable looting activities in the shelters.
Volume I. Primary report -- Volume II. Database appendixes (zip file).
Department Head: Kathleen A. Galvin.
Zip file contains volume 2, dataset appendixes.
Keywords: Gilligan's Island Site (Colo.); Fort Carson (Colo.); Fremont County (Colo.) -- Antiquities; Middle Archaic; developmental periods; Late Archaic; Gilligan's Island site; 5FN1592; Fort Carson Military Reservation; shelter occupation; prehistoric life; Excavations (Archaeology) -- Colorado -- Fremont County